2012
DOI: 10.1016/j.bcp.2012.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelin receptor type B: Structure, function and dysregulation in vascular disease

Abstract: Endothelin-1 (ET-1) is a major regulator of vascular function, acting via both endothelin receptor type A (ETAR) and type B (ETBR). Although the role of ETAR in vascular smooth muscle (VSM) contraction has been studied, little is known about ETBR. ETBR is a G-protein coupled receptor with a molecular mass of ~50 kDa and 442 amino acids arranged in seven transmembrane domains. Alternative splice variants of ETBR and heterodimerization and cross-talk with ETAR may affect the receptor function. ETBR has been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
133
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 136 publications
(193 reference statements)
2
133
0
Order By: Relevance
“…These data suggest that increased cerebrovascular ET-1-mediated constrictions after OSA involves increased ROCK-mediated Ca 2+ sensitization ( Figure 7) and are consistent with the previous studies showing that activation of G 12/13 protein by ET B R enhances Ca 2+ sensitivity through ROCK. 7 In conclusion, we show that OSA significantly alters the constrictor response of cerebral arteries to ET-1. We observe increased ET-1 sensitivity in the absence of elevated BP or upregulation of key components of the ET-1/ET-1 receptor system.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These data suggest that increased cerebrovascular ET-1-mediated constrictions after OSA involves increased ROCK-mediated Ca 2+ sensitization ( Figure 7) and are consistent with the previous studies showing that activation of G 12/13 protein by ET B R enhances Ca 2+ sensitivity through ROCK. 7 In conclusion, we show that OSA significantly alters the constrictor response of cerebral arteries to ET-1. We observe increased ET-1 sensitivity in the absence of elevated BP or upregulation of key components of the ET-1/ET-1 receptor system.…”
Section: Discussionmentioning
confidence: 54%
“…16 It should be noted that ET B R has been shown to signal through G q11,12 and 13 , which are involved in the activation of both TRPCs and ROCK. 7,34,35 Given that inhibition of either TRPCs or ROCK alone fully restored vascular contractility to sham levels, we propose that these mechanisms may act in series. Although further investigation is required, ROCK has been shown to activate TRPCs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on these findings, we cannot exclude the participation of both types of Ca 2ϩ pools. Moreover, we found that the phospholipase C inhibitor U-73122 abolished the effect of ET-1; this is not surprising, given that ET B receptors couple to G q/11 (11) and that phospholipase C is present in the lysosomal membrane (51 (52,53) and endothelial NO synthase phosphorylation (54), which leads to the release of the vasorelaxant mediator NO. Indeed, intracellular administration of ET-1 resulted in NO release, an effect that was completely contingent on endothelial NO synthase.…”
Section: Discussionmentioning
confidence: 56%
“…Accordingly, various types of receptors, including GPCRs, have been reported to trigger signal transduction pathways upon their endolysosomal activation (1,47). However, the ET-1 binding pocket on the ET B receptor is located on the N-terminal side, thus within the lysosomal lumen (11). We have previously demonstrated that angiotensin II is transferred inside the endolysosomal vesicles via microautophagy (17), a process in which soluble cytosolic molecules are engulfed (48).…”
Section: Discussionmentioning
confidence: 99%